Del Pino, Fermín (ed.). "The anthropologist as author, or of the reflexivity of the Euro-American subject". Madrid: csic. (thematic number of the Revista de dialectología y tradiciones populares. 2008, volume 63, n ° 1) - Rivera Andía, Juan Javier (2009)
The review does not present a summary